Canary Wharf : financing and placemaking - Goetzmann, William N.; Rosenthal, Jean W., 1945-; Elias, Jaan (London : Yale School of Management, 2017)
Over nearly thirty years, developers of London's Canary Wharf had navigated the project through a variety of economic, financial, and construction crises, at times facing ruin. By 2017, the project was widely recognized as a success - an internationally recognized financial district of 16 million square feet accommodating over 100,000 workers. Yet storm clouds once again threatened the Estate, as the owners had to grapple with the fallout from the U.K.'s decision to leave the European Union (Brexit) and the rise of fintech.
Originally published in Goetzmann, W. N., Rosenthal, J. W., & Elias, J. (2017). Canary Wharf: Financing and placemaking. Case 17-017. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/canary-wharf.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Financial institutions -- England -- London; Stock exchanges -- England -- London; Capital market -- England -- London; Canary Wharf (London, England)